Study of the Mechanical Properties of a Conglomerate. (2016) - Bonetto, Sabrina; Comina, Cesare; Colombero, Chiara; Pierre, Francesco Dela; Ferrero, Anna Maria; Giordano, Nicolò; Rispoli, Andrea; Vagnon, Federico
Abstract: This paper is devoted to the study of a conglomerate rock formation (Molare Formation) outcropping in southern Piedmont that forms a natural arch of environmental interest. Awareness with respect to the stability of this structure emerged after some intense rains which caused small collapses at the arch foot. The need for a proper characterization of the material in its natural state and its deterioration following increased water saturation is needed. A multidisciplinary approach based on the integration of both in situ and laboratory geophysical tests for the assessment of the rock structure at different scales was performed. Geological surveys together with seismic tomography and GPR have been executed on site. Petrographical and compositional studies of the matrix, ultrasonic pulse velocity measurements, electrical resistivity determinations and standard UCS test on large specimens are under development in laboratory.